1997
DOI: 10.1073/pnas.94.16.8652
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenicity in Escherichia coli of the major DNA adduct derived from the endogenous mutagen malondialdehyde

Abstract: The spectrum of mutations induced by the naturally occurring DNA adduct pyrimido[1,2-␣]purin-10(3H)-one (M 1 G) was determined by site-specific approaches using M13 vectors replicated in Escherichia coli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
167
1
6

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 163 publications
(188 citation statements)
references
References 33 publications
14
167
1
6
Order By: Relevance
“…The involvement of NER is indicated by both increased mutation frequency and increased adducted-template replication in the NER-deficient strains. Similarly, it was recently shown (84)(85)(86)(87) that E. coli NER is also implicated in repair of the major acrolein-derived DNA adduct, g-HO-PdG (Fig. 3), which has been detected in DNA from healthy human tissues.…”
Section: Repair Of Six-membered Propano-g Derivatives and M 1 G By Thsupporting
confidence: 59%
See 2 more Smart Citations
“…The involvement of NER is indicated by both increased mutation frequency and increased adducted-template replication in the NER-deficient strains. Similarly, it was recently shown (84)(85)(86)(87) that E. coli NER is also implicated in repair of the major acrolein-derived DNA adduct, g-HO-PdG (Fig. 3), which has been detected in DNA from healthy human tissues.…”
Section: Repair Of Six-membered Propano-g Derivatives and M 1 G By Thsupporting
confidence: 59%
“…Overlapping repair also exists for some exocyclic adducts, since, chemically, most of the exocyclic adducts are nonbulky, which makes them potential targets for various pathways. For example, both NER and MMR are implicated in repair of PdG and M 1 G, (83,86,91) whereas both BER and NER can act on 1,N 2 -eG. (36,48,72,76) Overlap between glycosylases is also common as examplified by the in vitro identification of the eC-activity in three human DNA glycosylase, TDG, SMUG1 and MBD4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…M 1 dG is mutagenic in bacterial and mammalian cells (13)(14)(15)(16) and can be extracted from the genomic DNA of humans and animals (17)(18)(19). M 1 -dG is reported to be a substrate for the nucleotide excision repair pathway (NER), which accounts for its appearance in human urine (13,20).…”
Section: Introductionmentioning
confidence: 99%
“…M 1 dG is excised from genomic DNA by nucleotide excision repair (NER) and has been detected in the urine of healthy humans. [3,4] Urinary analysis is a convenient, noninvasive approach for determining adduct burden, making M 1 dG an attractive biomarker for oxidative stress. We recently reported that M 1 dG is a substrate for cellular oxidases and is rapidly converted to 3-(2-deoxy-β-D-erythropentofuranosyl)-3,4-dihydropyrimido[1,2-α]purine-6,10-dione (6-oxo-M 1 dG) after NER excision from DNA (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%